2008
DOI: 10.1002/ird.450
|View full text |Cite
|
Sign up to set email alerts
|

Predicting alfalfa hay production as related to water distribution functions

Abstract: The present study was carried out to evaluate two crop water production models for estimating the effects of irrigation uniformity on alfalfa hay yields. The models included the ratio of actual to maximum hay yield, two parameters of the sprinkler water uniformity, and the ratio of gross to required irrigation. Measured data from three experimental plots of a farm located in Varamin, Iran, were used for the evaluation of the proposed models. Comparisons showed that the results from both models were in good agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…In this way, considering irrigation distribution was able to improve model predictions of average maize yield within an irrigated field. The results of Montazar et al (2010) in alfalfa support our finding, as they concluded that alfalfa forage production was better predicted using a normal distribution of irrigation water, as compared with simulations with a uniform amount of water applied, that tended to overpredict alfalfa yield. The accurate predictions in the present experiment indicate that daily simulation of the water balance and its consequences on maize yield was crucial to…”
Section: Taking Into Account Irrigation Uniformity Improves Predictiosupporting
confidence: 85%
“…In this way, considering irrigation distribution was able to improve model predictions of average maize yield within an irrigated field. The results of Montazar et al (2010) in alfalfa support our finding, as they concluded that alfalfa forage production was better predicted using a normal distribution of irrigation water, as compared with simulations with a uniform amount of water applied, that tended to overpredict alfalfa yield. The accurate predictions in the present experiment indicate that daily simulation of the water balance and its consequences on maize yield was crucial to…”
Section: Taking Into Account Irrigation Uniformity Improves Predictiosupporting
confidence: 85%